Bezpieczeństwo państwa — czynniki miękkie - Paluch, Alicja; Spustek, Henryk (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
This article is divided into three parts, in the first part it is explained what social capital is, and its role in national security is depicted. In the second part, the problem of the importance of social rules in the construction of social capital is discussed. The third part of the article is the culmination of the analysis and shows the role of soft factors in the process of building national security. The quality of social capital depends on how the society works. It is strongly related to other pillars of state security, including the armed forces. The most important message from the content of this article is the statement: a strong society means a safe state.
Keywords: bezpieczeństwo narodowe; kapitał społeczny; czynniki miękkie